Analisis Penggunaan Technology Acceptance Model (TAM) Untuk Mengukur Minat Mahasiswa Dalam Menggunakan Sistem E-Learning (Survey Pada Mahasiswa FEB Jurusan Akuntansi S1 Universitas Mercu Buana) - Wahyu Sugiarni; Fardinal Fardinal (Jurnal Pena-Mas Akuntansi, 2020)
This research aims to know the factors that affect student interest in using the e-learning system at the University of Mercu Buana Jakarta. The model used to understand students' interest in using e-learning system is Technology Acceptance Model (TAM) with 4 (four) constructs namely Perceived Usefulness / (PU), Perceived Ease of Use (PEOU), Attitude toward system usage (Attitude Towards Using / ATU), and behavioral use of the system (Behavioral Intention to Use / BITU). The type of data used is the primary data obtained from the closed questionnaire. The type of sampling used is stratified random sampling. The sample size is 97 students, calculated using the Slovin formula with 10% significance. The data obtained were analyzed by Partial Least Square (PLS) method using SmartPLS software. Based on data analysis, the following results are obtained: (1) Perceived Ease of Use (PEOU) has a significant effect on Perceived Usefulness (PU); (2) Perceived Ease of Use (PEOU) has a significant effect on Attitude Toward Using (ATU); (3) Perceived Usefulness (PU) has a significant effect on Attitude Toward Using (ATU); (4) Perceived Usefulness (PU) has a significant effect on Behavioral Intention to use (BITU); (5) Attitude Toward Using (ATU) has a significant effect on Behavioral Intention to Use (BITU).e-Learning System, Technology Acceptance Model (TAM), Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Towards Using  (ATU), Behavioral Intention to Use (BITU)